Three-dimensional analysis of embankments on soft soils incorporating vertical drains by finite element method - José Leitão Borges (2004)
Three-dimensional behaviour of an embankment on soft soils incorporating vertical drains is analysed by a numerical model based on the finite element method. The model, which incorporates the Biots consolidation theory (coupled formulation of the flow and equilibrium equations) and constitutive relations simulated by the pqh critical state model, is applied on both the embankment with vertical drains (three-dimensional analysis) and the same problem but without vertical drains (two-dimensional analysis). Special emphasis is given to the analysis, during and after the construction period, of the excess pore pressures, settlements, horizontal displacements and stress levels.